2019
DOI: 10.1016/j.jss.2019.110416
|View full text |Cite
|
Sign up to set email alerts
|

A topological analysis of communication channels for knowledge sharing in contemporary GitHub projects

Abstract: With over 28 million developers, success of the GitHub collaborative platform is highlighted through an abundance of communication channels among contemporary software projects. Knowledge is broken into two forms and its sharing (through communication channels) can be described as externalization or combination by the SECI model. Such platforms have revolutionized the way developers work, introducing new channels to share knowledge in the form of pull requests, issues and wikis. It is unclear how these channel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…However, there are also projects using old channels like ICQ. Tantisuwankul et al have shown that the used GitHub channels change and evolve over time [32]. It looks like this is the same for other communication channels as well.…”
Section: Rq 1: What Types Of Communicationmentioning
confidence: 84%
See 1 more Smart Citation
“…However, there are also projects using old channels like ICQ. Tantisuwankul et al have shown that the used GitHub channels change and evolve over time [32]. It looks like this is the same for other communication channels as well.…”
Section: Rq 1: What Types Of Communicationmentioning
confidence: 84%
“…Tantisuwankul et al [32] showed that contemporary GitHub projects tend to offer multiple communication channels. These channels are constantly changing, meaning that new channels get adopted, and other channels are not used anymore.…”
Section: Research Objectivementioning
confidence: 99%
“…TDA has been applied in various fields such as an analysis of bacteria survival in soils (Ibekwe et al 2014) and the performance of NBA players (Lum et al 2013). Most recently in software engineering, Lertwittayatrai et al (2017) used TDA to distinguish characteristics of JavaScript npm libraries (such as licence usage, dependency usage and so on) and Tantisuwankul et al (2019) to analyze the implementation of such communication channels over open source software projects. We use TDA to provide a visual representation that shows (i) the activity levels for each feature and (ii) show the contributor activity across systems, especially with respect to forums.…”
Section: Shape Of Contributors' Participationmentioning
confidence: 99%
“…This will also enable developers to provide a community-related information or announcement. As reported by Tantisuwankul et al [25] that software projects tend to adopt communication channel for both capturing new knowledge and updating existing knowledge, and since the information or announcement that specifically relates to the software projects is important to share amongst the community, providing an NS-specific discussion forum is necessary.…”
Section: Software Development Projectsmentioning
confidence: 99%